2016
DOI: 10.1097/rli.0000000000000211
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Arterial Phase in Gadoxetic Acid–Enhanced Liver Magnetic Resonance Imaging

Abstract: The objective analysis of respiratory patterns during a breath-hold is feasible and useful for evaluating gadoxetic acid-related dyspnea and its effect on image quality analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…Fifth, the effect of IPPP was measured only indirectly based on RM image artefacts, which is prone to be biased by subjective interpretation. Although the inter-reader agreement in our study was very good to excellent and matched the results of a recent multi-center trial [36], the assessment of IPPP by dedicated patient questionnaires, respiratory waveform analysis [7,10,14,37,38] or including classification of hyper-and hypovascular liver lesions might have added valuable information and should be addressed in future studies.…”
Section: Plos Onesupporting
confidence: 85%
“…Fifth, the effect of IPPP was measured only indirectly based on RM image artefacts, which is prone to be biased by subjective interpretation. Although the inter-reader agreement in our study was very good to excellent and matched the results of a recent multi-center trial [36], the assessment of IPPP by dedicated patient questionnaires, respiratory waveform analysis [7,10,14,37,38] or including classification of hyper-and hypovascular liver lesions might have added valuable information and should be addressed in future studies.…”
Section: Plos Onesupporting
confidence: 85%
“…The presence of such artefacts has been reported in a wide range of patients depending on the case series (from 2.4% to 18%). [195][196][197] Whether these artefacts hamper the detection of lesion vascularity on arterial phase has not been not clearly established yet.…”
Section: Specific Issue With Gadoxetic-enhanced Mrimentioning
confidence: 99%
“…Motosugi et al found a significantly higher risk of TSM in patients with a high BMI [30]. Hayashi et al confirmed that body weight contributes to the occurrence of TSM [11].…”
Section: Potential Individual Risk Factorsmentioning
confidence: 95%
“…Also, no significant correlation was identified between changes in blood oxygen saturation and the occurrence of TSM [7,11,13,30], neither did any of the studies reveal a significant change in heart rate after injection of gadoxetate disodium [7,11,13]. ▶ Table 4 Frequency of TSM and potential risk factors…”
Section: Effects Of Gadoxetic Disodium Injection On Physiological Parmentioning
confidence: 97%
See 1 more Smart Citation